HMD-Based Virtual and Augmented Reality in Medical Education: A Systematic Review - Xu, Xuanhui; Mangina, Eleni; Campbell, Abraham G. (Frontiers in Virtual Reality, 2021)
Background: Virtual Reality (VR) and Augmented Reality (AR) technologies provide a novel experiential learning environment that can revolutionise medical education. These technologies have limitless potential as they provide in effect an infinite number of anatomical models to aid in foundational medical education. The 3D teaching models used within these environments are generated from medical data such as Magnetic Resonance Imaging (MRI), or Computed Tomography (CT), which can be dissected and regenerated without limitations. Methods: A systematic review was carried out for existing articles until 11/02/2020 in Embase, PubMed, Scopus, ProQuest, Cochrane Reviews, CNKI, OneSearch (University College Dublin Library) using search term: (Virtual Reality OR Augmented Reality OR mixed reality) AND ("head-mounted" OR "face-mounted" OR "helmet-mounted" OR "head-worn" OR oculus OR vive OR HTC OR hololens OR "smart glasses" OR headset AND (training OR teaching OR education)) AND (anatomy OR anatomical OR medicine OR medical OR clinic OR clinical OR surgery OR surgeon OR surgical) AND (trial OR experiment OR study OR randomized OR randomised OR controlled OR control) NOT (rehabilitation OR recovery OR treatment) NOT ("systematic review" OR "review of literature" OR "literature review"). PRISMA guidelines were adhered to in reporting the results. All studies examining the people who are or were medical-related (novel or expert users) were included. Result: The electronic searches generated a total of 1241 studies. After removing duplicates, 848 remained. Of those, 801 studies were excluded because the papers did not meet the criteria after reviewing the abstract. The full text of the remaining 47 papers was reviewed. After applying inclusion criteria and exclusion criteria, a total of 17 studies (1050 participants) were identified for inclusion in the review. Conclusions: The systematic review provides the current state of the art on head-mounted device applications in medical education. Moreover, the paper discusses trends towards the future and directions for further research in head-mounted VR and AR for medical anatomy education.